2021
DOI: 10.3389/fcvm.2021.630968
|View full text |Cite
|
Sign up to set email alerts
|

Updated Role of Neuropeptide Y in Nicotine-Induced Endothelial Dysfunction and Atherosclerosis

Abstract: Cardiovascular disease is the leading cause of death worldwide. Endothelial dysfunction of the arterial vasculature plays a pivotal role in cardiovascular pathogenesis. Nicotine-induced endothelial dysfunction substantially contributes to the development of arteriosclerotic cardiovascular disease. Nicotine promotes oxidative inflammation, thrombosis, pathological angiogenesis, and vasoconstriction, and induces insulin resistance. However, the exact mechanism through which nicotine induces endothelial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 119 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…These factors will be harmful to the arteries, and promote the development of atherosclerosis (67,74). Other studies have found that Neuropeptide Y (NPY) is a mediator of vascular lipid metabolism disorder under chronic stress and a risk factor for stress-induced lipid metabolic syndrome and atherosclerosis (75)(76)(77)(78). Understanding how neuropeptide Y and its homologous receptors regulate lipid metabolism may provide new ideas for the study of the mechanism and treatment of atherosclerosis (79,80).…”
Section: Disorder Of Lipid Metabolism In Atherosclerosis Under Chronic Stressmentioning
confidence: 99%
“…These factors will be harmful to the arteries, and promote the development of atherosclerosis (67,74). Other studies have found that Neuropeptide Y (NPY) is a mediator of vascular lipid metabolism disorder under chronic stress and a risk factor for stress-induced lipid metabolic syndrome and atherosclerosis (75)(76)(77)(78). Understanding how neuropeptide Y and its homologous receptors regulate lipid metabolism may provide new ideas for the study of the mechanism and treatment of atherosclerosis (79,80).…”
Section: Disorder Of Lipid Metabolism In Atherosclerosis Under Chronic Stressmentioning
confidence: 99%
“…26 Overexpression of NPY in perivascular regions can promote plaque development and coronary atherosclerotic formation. 27 In this work, we developed a multimodal sensing platform to simultaneously detect Na + , AA, and NPY in sweat, toward a real-time personalized evaluation of the cardiovascular health status (Figure 1). Herein, carbon quantum dots (CQDs) are chosen as electrode substrates to immobilize enzymes and provide reactive sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Abnormal Na + levels can lead to unstable intracardiac metabolism resulting in myocardial ischemia and arrhythmias. , AA shows the capability of preventing atherosclerosis formation, stimulating blood coagulation function, and declining lipid levels in the blood. , NPY is an expressive neurotransmitter capable of modulating the immune and metabolic responses associated with an atherosclerosis degree . Overexpression of NPY in perivascular regions can promote plaque development and coronary atherosclerotic formation …”
Section: Introductionmentioning
confidence: 99%
“…Although the best medical treatment and coronary artery reperfusion therapy improve the survival of patients, coronary heart disease is still one of the main causes of morbidity and mortality worldwide. Acute myocardial infarction (AMI) is characterized by the loss of cardiomyocytes, scarring, ventricular remodelling, and can develop into end-stage heart failure [ 1 ]. Therefore, effective cardiac repair is essential for the recovery of cardiac function after AMI.…”
Section: Introductionmentioning
confidence: 99%